Answer:
53
Step-by-step explanation:
72 = x + 3x - 4
72 = 4x - 4
72 + 4 = 4x - 4 + 4
76 = 4x
76/4 = 4x/4
x = 19
3(19) - 4 = 53
Hope this helps!
Answer:
(x - 1)(x + 1)(x² + 1)
Step-by-step explanation:
Step 1: Factor Difference of Squares
(x² - 1)(x² + 1)
Step 2: Factor Difference of Squares for non-complex binomial root
(x - 1)(x + 1)(x² + 1)
And we have our answer!
Answer:
(x+1)(x-1)(x+3)(x-3)
Step-by-step explanation:
x4-10x^2+9
Group expression so that the coefficients of the x^2 terms add up to +9.
= x^4 -9x^2 - x^2+9
match coefficients in both groups
= x^4 -9x^2 - (x^2-9)
factor each group
= x^2 (x^2-9) - 1(x^2-9)
now factor out the common factor (x^2-9)
= (x^2-1)(x^2-9)
Finally, factor each quadratic factor
= (x+1)(x-1)(x+3)(x-3)
Answer:
false
Step-by-step explanation:
Based on the information provided we can say that this is false. Since it is a board game and no actual information regarding each players position in the game has been presented, then each player has an equal chance of winning each game. Therefore since there is a total of 3 players the percent chance of winning each game for each player is 33% (100 / 3 = 33)